Application of telemedicine system for older adults postoperative patients in community: a feasibility study - Quan-Peng Wang; Wan-Ying Chang; Man-Man Han; Ye-Xiao Hu; Sai-Sai Lin; Ye-Chun Gu (Frontiers Media S.A., 2024)
PurposeIn response to the growing challenges posed by an aging society, a telemedicine system was developed specifically for older adults postoperative patients, and its effectiveness was thoroughly investigated.MethodsBetween May 2020 and May 2022, a total of 88 older adults postoperative patients were enrolled and randomly allocated into an experimental group and a control group. The experimental group received telemedicine services after discharge, while the control group received conventional medical services following the traditional protocol. One month after discharge, various indicators were evaluated for both groups, including number of visits, medical expenditures, postoperative recovery, anxiety, depression and satisfaction.ResultsThe number of visits and medical expenditures of the experimental group were less than those of the control group [1 (0, 1) vs. 1 (1, 2), Z = −3.977, p < 0.001; 25.25 (0.00, 277.40) yuan vs. 174.65 (49.63, 446.10) yuan, Z = −2.150, p = 0.032]. In both groups, there were 2 cases of incision infection, respectively. No significant difference was observed between the two groups (Fisher χ2, p = 0.259). In both groups, there was no instance of incision bleeding, incision dehiscence, readmission, or reoperation. Additionally, there was no significant difference in physical status between the two groups at discharge and after discharge (66.06 ± 8.92 vs. 65.45 ± 7.39 t = 0.287, p = 0.775; 73.33 ± 9.97 vs. 70.91 ± 7.50, t = 1.202, p = 0.235). And there was no significant difference in the change of physical status between the two groups after discharge [10.00 (0.00, 10.00) vs. 5.00 (0.00, 10.00), Z = −1.077, p = 0.281]. There was no significant difference in body weight change between the two groups after discharge [1.05 (0.38, 1.60) Kg vs. 0.80 (0.50, 1.43) Kg, Z = −0.265, p = 0.791]. There was no significant difference in the levels of anxiety and depression between the two groups at discharge (45.64 ± 8.10 vs. 44.60 ± 8.24, t = 0.520, p = 0.604, 48.33 ± 8.46 vs. 47.50 ± 6.85, t = 0.418, p = 0.677). But the levels of anxiety and depression in the experimental group were lower than those in the control group after discharge (34.92 ± 7.38 vs. 39.03 ± 8.42, t = −2.183, p = 0.032, 37.86 ± 7.29 vs. 41.93 ± 7.13, t = −2.281, p = 0.025); The change of anxiety level and depression level of the experimental group were more than those of the control group [−10.00 (−11.25, −8.75) vs. −5.00 (−7.81, −3.75), Z = −5.277, p < 0.001; −10.00 (−12.50, −7.50) vs. −5.00 (−7.75, −3.44), Z = −4.596, p < 0.001]. The level of satisfaction regarding medical services, daily care, and psychological comfort was higher in the experimental group compared to the control group [3 (3, 3.25) vs. 2 (1, 2), Z = −5.931, p < 0.001; 3 (3, 4) vs. 3 (2, 3), Z = −2.286, p = 0.022; 2 (1, 3) vs. 1 (0.75, 2), Z = −2.081, p = 0.037].ConclusionIn the context of an aging society, telemedicine system can offer improved healthcare to older adults postoperative patients. This includes benefits such as reducing number of visits, saving medical expenditures, enhancing psychological comfort and daily care.